Dissemination and genome analysis of high-level ceftriaxone-resistant penA 60.001 Neisseria gonorrhoeae strains from the Guangdong Gonococcal antibiotics susceptibility Programme (GD-GASP), 2016–2019. Issue 1 (31st December 2022) - Lin, Xiaomian; Chen, Wentao; Xie, Qinghui; Yu, Yuqi; Liao, Yiwen; Feng, Zhanjin; Qin, Xiaolin; Wu, Xingzhong; Tang, Sanmei; Zheng, Heping
ABSTRACT: Background: After Neisseria gonorrhoeae FC428 was first found in Japan, ceftriaxone-resistant strains disseminated globally, and the gonococcal resistance rate increased remarkably. Epidemiological investigations are greatly significant for the analysis of antimicrobial resistance (AMR) trends, molecular features and evolution. Objectives: To clarify the AMR trend from 2016–2019 and reveal the molecular characteristics and evolution of ceftriaxone-resistant penA 60.001 isolates. Methods: The minimum inhibitory concentrations (MICs) of antibiotics against 4113 isolates were detected by the agar dilution method. N. gonorrhoeae multiantigen sequence typing (NG-MAST), multilocus sequence typing (MLST) and N.gonorrhoeae sequence typing for antimicrobial resistance (NG-STAR) were used to identify the sequence types. Genome analysis was conducted to analyze resistance genes, virulence factors, and evolutionary sources. Results: Isolates with decreased ceftriaxone susceptibility have increased from 2.05% (2016) to 16.18% (2019). Six ceftriaxone-resistant isolates possessing penA 60.001 appeared in Guangdong Province, and were resistant to ceftriaxone, penicillin, tetracycline, ciprofloxacin and cefixime, but susceptible to azithromycin and spectinomycin. Single-nucleotide polymorphisms (SNPs) in the porB gene were the major cause of different NG-MAST types. ST1903 was the main NG-STAR genotype and only strain-ZH545 was ST7365, with molecular features consistent with the MICs. Furthermore, different MLSTs suggested diverse evolutionary sources. Genome analysis revealed a set of virulence factors along with the resistance genes " penA " and " blaTEM-1B ". Half of penA 60.001 strains were fully mixed with global FC428-related strains. Conclusions: Global FC428-related clones have disseminated across Guangdong, possibly causing decreased ceftriaxone susceptibility. Enhanced gonococcal surveillance will help elucidate the trajectory of transmission and curb further dissemination.